1988
DOI: 10.1002/ijc.2910420424
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the human pancreatic adenocarcinoma cell line (Capan‐1) in culture and co‐culture with fibroblasts dome formation

Abstract: This study was designed to investigate differentiation of human pancreatic duct carcinoma cells (Capan-1) in vitro. Observations on live cells, and electron microscopic examination, together with enzymological and immunocytochemical methods, have demonstrated that these cells differentiate spontaneously at an early stage. The cells are seen to be joined by apical junctions. High ATPase activity can be detected in the basolateral membranes, and the cells secrete a gastric type mucin (MI) bearing acidic groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…All cell lines were routinely grown in RPMI-1640 medium supplemented with 15% FCS for the CAPAN-1 cell line as described by Levrat et al [20]; with 10% FCS for the CFPAC cell lines. Media were supplemented with penicillin (100 units/ml), streptomycin (100 ~g/ml) and fungizone (0.25 mg/ml).…”
Section: Cell Culturementioning
confidence: 99%
“…All cell lines were routinely grown in RPMI-1640 medium supplemented with 15% FCS for the CAPAN-1 cell line as described by Levrat et al [20]; with 10% FCS for the CFPAC cell lines. Media were supplemented with penicillin (100 units/ml), streptomycin (100 ~g/ml) and fungizone (0.25 mg/ml).…”
Section: Cell Culturementioning
confidence: 99%
“…Capan-1 cells represent an excellent model for the in vitro study of human cancerous pancreatic duct cells, as despite their neoplastic transformation, they retain a polarized morphology and the ability to secrete HCO 3 À ions 55,56 and M1 mucins (MUC5AC). 57-59 These cells express Fas, but depending to authors, are sensitive [47][48][49] or resistant 50,51 to Fas-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CAPAN-1, the pancreatic duct cell line, provides a useful in vitro model for the study of the human pancreatic ductal secretory mechanisms since it has been shown to possess most of the properties of pancreatic ductal epithelial cells, [5][6][7] and contain apical Cl Ϫ channels that are involved in HCO 3 Ϫ secretion. 8,9) HCO 3 Ϫ secreted by CAPAN-1 cells could be measured using the short-circuit current technique.…”
mentioning
confidence: 99%